2017
DOI: 10.1103/physrevapplied.8.044019
|View full text |Cite
|
Sign up to set email alerts
|

Miniature Cavity-Enhanced Diamond Magnetometer

Abstract: International audienceWe present a highly sensitive miniaturized cavity-enhanced room-temperature magnetic-field sensor based on nitrogen-vacancy centers in diamond. The magnetic resonance signal is detected by probing absorption on the 1042-nm spin-singlet transition. To improve the absorptive signal the diamond is placed in an optical resonator. The device has a magnetic-field sensitivity of 28  pT/Hz, a projected photon shot-noise-limited sensitivity of 22  pT/Hz, and an estimated quantum projection-noise-l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
94
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 21 publications
2
94
0
Order By: Relevance
“…We have shown that magnetometry based on the IR absorption associated to the singlet states of the NV − center can be implemented by integrating a diamond sample containing the NV centers inside an external half-VCSEL cavity. This scheme does not require a narrow linewidth stabilized IR laser as in realizations based on multi-pass absorption in a resonant passive cavity [16]. Compared to previous proposals consisting of a diamond laser using the NV − centers for optical amplification, the detrimental effects of both the parasitic ESA by the triplet excited state and the photoconversion to the NV 0 charge state are also circumvented since the optical gain is obtained from an independent system.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that magnetometry based on the IR absorption associated to the singlet states of the NV − center can be implemented by integrating a diamond sample containing the NV centers inside an external half-VCSEL cavity. This scheme does not require a narrow linewidth stabilized IR laser as in realizations based on multi-pass absorption in a resonant passive cavity [16]. Compared to previous proposals consisting of a diamond laser using the NV − centers for optical amplification, the detrimental effects of both the parasitic ESA by the triplet excited state and the photoconversion to the NV 0 charge state are also circumvented since the optical gain is obtained from an independent system.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, negatively charged nitrogen-vacancy (NV) centers in single-crystal diamond provide high-sensitivity magnetic sensing and high-resolution imaging [9][10][11] . To date, diamondbased vector magnetometers have been based on using the optically detected magnetic resonance (ODMR) technique with the requirement of applying microwaves (MWs) sequentially or simultaneously [12][13][14] .…”
mentioning
confidence: 99%
“…In systems containing an addressable spin of interest ("the spin qubit"), such as phosphorus donors in silicon and nitrogenvacancy (NV) centers in diamond, such spin-bath noise acts as the main decoherence source of the system [1][2][3][4][5]. The first step towards enabling full coherent control of such spin qubits, whose applications range from quantum information processing [6][7][8][9] to metrology [10][11][12][13][14][15], involves full spectral analysis of the spin-bath noise.…”
Section: Introductionmentioning
confidence: 99%